Synchronous Malignancies - Unveiling the Genetic Overlap: A Rare Case - Ayush, Saxena; Anshu, Gupta; Salony, Mittal (Journal of Neonatal Surgery, 2025)
Synchronous thyroid and breast malignancies are infrequently reported in literature. Their coexistence do indicate some common genetic and/or hormonal link between the two. We encountered a similar case at our institute and intended it to contribute to the existing literature. As, ongoing research and case reporting will provide more insights into the complexities of these simultaneous cancers and will also help in creating more effective management strategies.